"Just tensions left, right and centre": assessing the social impact of international migration on deindustrialized locale. Issue 15 (8th December 2021) - Lloyd, Anthony; Devanney, Carol; Wattis, Louise; Bell, Victoria
ABSTRACT: Deindustrialization wrought socio-economic and cultural change throughout the UK, Western Europe and the USA. Within some deindustrialized zones, multiple indices of deprivation rise significantly which presents complex and interrelated social problems including poverty, unemployment, poor quality private rented housing, complex physical and mental health problems, and crime. The austerity agenda further exacerbates these problems, cuts local support services, and further entrenches the myriad issues embedded in post-industrial communities. This paper draws on a funded research project in a deindustrialized town in the North East of England designed to measure the impact of migration on the settled community. The project found advantages to inward migration alongside increased community tension where poor neighbourhoods yet to recover from long-term deindustrialization saw a rapid increase of international migrants. These tensions represent competition for scarce resources amongst the fragmented multi-ethnic working class trying to get by in areas of "permanent recession".